2020
DOI: 10.1042/bsr20191488
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of SRPK2, Numb and p53 in the malignant biology and chemosensitivity of colorectal cancer

Abstract: Serine-arginine protein kinase 2 (SRPK2) is aberrantly expressed in human malignancies including colorectal cancer (CRC). However, little is known about the molecular mechanisms, and the role of SRPK2 in chemosensitivity remains unexplored in CRC. We recently showed that SRPK2 promotes pancreatic cancer progression by down-regulating Numb and p53. Therefore, we investigated the cooperation between SRPK2, Numb and p53 in the cell migration, invasion and chemosensitivity of CRC in vitro. Here, we showed that SRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Meanwhile, Numb-PRRS overexpression was associated with tumor high differentiation, indicating its pro-differentiation and tumor-suppressive role in the progression of PC based on our current and previous studies [ 19 , 20 , 25 ]. Interestingly, Numb-PRRL was overexpressed in hepatocellular carcinoma [ 14 ], medulloblastoma [ 10 , 26 ] and invasive urothelial carcinoma of the bladder [ 27 ], but exhibited low expression in breast [ 11 ] and lung cancers [ 12 ]. Therefore, the unbalanced distribution of Numb isoforms contributes to the distinguished role of total Numb protein in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Numb-PRRS overexpression was associated with tumor high differentiation, indicating its pro-differentiation and tumor-suppressive role in the progression of PC based on our current and previous studies [ 19 , 20 , 25 ]. Interestingly, Numb-PRRL was overexpressed in hepatocellular carcinoma [ 14 ], medulloblastoma [ 10 , 26 ] and invasive urothelial carcinoma of the bladder [ 27 ], but exhibited low expression in breast [ 11 ] and lung cancers [ 12 ]. Therefore, the unbalanced distribution of Numb isoforms contributes to the distinguished role of total Numb protein in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It displayed complex and multiple functions including the control of asymmetric cell division and cell fate choice, endocytosis, cell adhesion and migration, ubiquitination of specific substrates, and a variety of signaling pathways (Notch, Hedgehog, MDM2-p53, and WNT signaling) [ 8 10 ]. Accumulated evidence showed that Numb acts as a tumor-suppressive role in medulloblastoma [ 10 ], breast cancer [ 11 ], non-small cell lung cancer (NSCLC) [ 12 ], ovarian cancer [ 13 ], and colorectal cancer [ 14 ]. On the other hand, overexpression of Numb was found in hepatocellular carcinoma [ 15 ], astrocytomas [ 16 ], and cervical squamous carcinoma cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence seems to suggest that SRPK2 plays a similar oncogenic role, albeit not much is known about SRSF2 compared to SRSF1. Most recently, SRPK2 expression was shown to be higher in colorectal cancer tumors compared to nontumor tissues, and was positively associated with tumor differentiation, primary tumor (T) stage, regional lymph nodes (N) stage, and UICC stage (59). The same authors showed that SRPK2 promotes pancreatic cancer progression by downregulating Numb and p53, and this negative regulation also occurred following 5-fluorouracil or cisplatin treatment in colorectal cancer cells [ (37,59).…”
Section: Sr Protein Phosphorylation and Splicing Regulation In Cancermentioning
confidence: 99%
“…Most recently, SRPK2 expression was shown to be higher in colorectal cancer tumors compared to nontumor tissues, and was positively associated with tumor differentiation, primary tumor (T) stage, regional lymph nodes (N) stage, and UICC stage (59). The same authors showed that SRPK2 promotes pancreatic cancer progression by downregulating Numb and p53, and this negative regulation also occurred following 5-fluorouracil or cisplatin treatment in colorectal cancer cells [ (37,59). Overexpression also increased cell migration and invasion, and decreased chemosensitivity to 5fluorouracil or cisplatin (59).…”
Section: Sr Protein Phosphorylation and Splicing Regulation In Cancermentioning
confidence: 99%
See 1 more Smart Citation